Dukungan Sosial Orang Tua Dan Minat Belajar Siswa Pada Masa Pandemi Covid-19 : Fenti Listiarum Juniar, Nurwahyuni Nasir - Fenti Listiarum Juniar; Nurwahyuni Nasir (Social Philanthropic, 2022)
This study was made to find out whether there is a relationship between the social support of parents and the learning interests of students of SMK Negeri 2 during the covid-19 pandemic in the city of Bekasi. The method used is quantitatively correlational. This research sample is 100 students of SMK Negeri 2 in the city of Bekasi. The data was obtained through the parents' social support scale and the learning interest scale. The results of this study showed that in spearman rho' correlation analysis showed a weak or probable relationship between parental social support and learning interests (value r=0.375** with p≤0.000). It concluded that parental social support correlated with learning interest in students.